Effect of MRE11 Loss on PARP-Inhibitor Sensitivity in Endometrial Cancer In Vitro - Romana Koppensteiner; Eleftherios P. Samartzis; Aurelia Noske; Adriana von Teichman; Ioannis Dedes; Myriam Gwerder; Patrick Imesch; Kristian Ikenberg; Holger Moch; Daniel Fink; Manuel Stucki; Konstantin J. Dedes (2014)
Aim of the study To evaluate the frequency of MRE11/RAD50/NBS1 (MRN)-complex loss of protein expression in endometrial cancers (EC) and to determine whether loss of MRE11 renders the cancer cells sensitive to Poly(ADP-ribose) polymerase (PARP)-inhibitory treatment. Methods MRN expression was examined in 521 samples of endometrial carcinomas and in 10 cancer cell lines. A putative mutation hotspot in the form of an intronic poly(T) allele in MRE11 was sequenced in selected cases (n = 26). Sensitivity to the PARP-inhibitor, BMN673 was tested in colony formation assays before and after MRE11 silencing using siRNA. Homologous recombination (HR) DNA repair was evaluated by RAD51-foci formation assay upon irradiation and drug treatment. Results Loss of MRE11 protein was found in 30.7% of EC tumours and significantly associated with loss of RAD50, NBS1 and mismatch repair protein expression. One endometrial cell line showed a markedly reduced MRE11 expression due to a homozygous poly(T) mutation of MRE11, thereby exhibiting an increased sensitivity to BMN673. MRE11 depletion sensitizes MRE11 expressing EC cell lines to the treatment with BMN673. The increased sensitivity to PARP-inhibition correlates with reduced RAD51 foci formation upon ionizing radiation in MRE11-depleted cells. Conclusion Loss of the MRE11 protein predicts sensitivity to PARP-inhibitor sensitivity in vitro, defining it as an additional synthetic lethal gene with PARP. The high incidence of MRE11 loss in ECs can be potentially exploited for PARP-inhibitor therapy. Furthermore, MRE11 protein expression using immunohistochemistry could be investigated as a predictive biomarker for PARP-inhibitor treatment.